The adult growth hormone multicentric retrospective observational study: a 24-month Italian experience of adherence monitoring via Easypod™ of recombinant growth hormone treatment in adult GH deficiency - Mancini, Antonio; Vergani, Edoardo; Bruno, Carmine; Giavoli, Claudia; Spaziani, Matteo; Isidori, Andrea M.; Arosio, Maura; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2023)
Non-compliance to recombinant human growth hormone (rhGH) treatment is universally recognized as a key detrimental factor to achieve the expected clinical outcomes in adult GH deficiency (aGHD). The Easypod™ electronic device allows objective measurement of adherence. Adherence to treatment has been reported to be related with IGF-1 levels and consequently with clinical satisfactory results. The aim of this multicentric, observational, retrospective, 24-month study, is to objectively assess aGHD patients' compliance to rhGH, using the Easypod™ device. Additionally, the study aims to compare the biochemical responses of adherent vs non-adherent patients.Forty-three patients (28 females and 15 males) affected by aGHD and equipped with Easypod™ from 3 Italian centers were included in the study. Adherence to treatment was defined as the proportion of injections correctly administered during the observational period, out of the expected total number of injections. All patients were evaluated for IGF-1, glucose, insulin, HOMA and QUICKI index, total/LDL/HDL cholesterol and triglycerides.Mean adherence rate was consistently under 85% across the 2-year observation period (73% at year 2). A trend toward significant difference in adherence was shown when comparing female and male patients (respectively 76% and 61%) after a 2-year period. Among the anamnestic features, the prescribed frequency of administration of rhGH and the number of administered therapies appeared to be the most relevant adherence-influencing factors. A strong direct correlation between IGF-1 z-score and adherence to rhGH therapy was detected in the whole population.Compliance to rhGH therapy is still a major issue in aGHD treatment. Adherence relates to therapy efficacy in aGHD. The use of Easypod™ could be beneficial for physicians to better manage aGHD patients and to achieve improved better biochemical and clinical responses.